Inovasi Pembelajaran Bahasa: Metode Storytelling Berbasis Media Visual untuk Meningkatkan Keterampilan Berbicara Siswa - Yusrizal, Yusrizal; Fatmawati, Fatmawati; Nst, Hadijah; Wulandari, Tia; Arif, M. (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Low speaking ability remains a problem that is often found among lower-grade elementary school students, so more engaging and participatory learning methods are needed to improve this skill. This study aims to analyze the impact of the illustrated storytelling method on students’ speaking skills. This study employed a quantitative approach with a quasi-experimental design, involving 30 second-grade students of SD Swasta Al-Washliyah Km. 6 who were divided into two groups, namely 15 students in the experimental group taught using the illustrated storytelling method and 15 students in the control group taught using the lecture method. Data were collected through observation and speaking skills tests, and were then analyzed through tests of normality, homogeneity, and hypothesis testing using the independent sample t-test and paired sample t-test at a significance level of 0.05. The results showed that the storytelling method based on visual media had a significant effect on improving students’ speaking ability. This was indicated by the results of the independent sample t-test with a significance value of 0.035 (Sig. < 0.05) and the results of the paired sample t-test in the experimental class with a significance value of 0.011 (Sig. < 0.05), which indicate a significant improvement in students’ speaking ability before and after the implementation of the method. These findings show that the illustrated storytelling method can be an effective learning alternative for improving students’ speaking skills, particularly in Indonesian language learning in the lower grades of elementary school.